The Development of Eco-Tahfiz In Malaysia: Bridging Islamic Education and Environmental Sustainability - Rekan, Abd. Aziz; Mokhtar, Mohd Istajib (Universitas Islam Negeri Mataram, 2025)
The Eco-Tahfiz initiative in Malaysia integrates Islamic education with environmental sustainability, offering a faith-based educational model that aligns with national priorities and global sustainability goals. This study examines the development of the Eco-Tahfiz initiative, focusing on its key drivers, challenges, and prospects through a qualitative methodology. The key enablers for the Eco-Tahfiz initiative include institutional support, integrating environmental themes into Islamic education, and alignment with cultural-religious values. Key barriers identified include limited teacher training, insufficient integration of intrinsic values, and the predominantly theoretical application of Fiqh al-Bī‘ah. To address these challenges, the study proposes inter-agency collaboration, leadership engagement, teacher capacity building, community participation, and a structured Eco-Tahfiz Action Plan to enhance the initiative's implementation and relevance across broader Muslim educational contexts.